Tracking key CAADP indicators and implementation processes [In the 2015 ATOR] - Bahiigwa, Godfrey; Benin, Samuel; Tefera, Wondwosen (International Food Policy Research Institute, 2016)
The revised CAADP Results Framework has 40 indicators for tracking progress across three levels. Level 1 includes the high-level outcomes and impacts to which agriculture contributes, including wealth creation; food security and nutrition; economic opportunities, poverty alleviation, and shared prosperity; and resilience and sustainability. Level 2 includes the outputs from interventions intended to transform the agriculture sector and achieve inclusive growth: improved agricultural production and productivity; increased intra-African regional trade and functional markets; expanded local agro-industry and value-chain development, inclusive of women and youth; increased resilience of livelihoods and improved management of risks in agriculture; and improved management of natural resources for sustainable agriculture. Level 3 includes inputs and processes required to strengthen systemic capacity to deliver CAADP results and create an enabling environment in which agricultural transformation can take place: effective and inclusive policy processes; effective and accountable institutions, including assessing implementation of policies and commitments; strengthened capacity for evidence-based planning, implementation, and review; improved multi-sectoral coordination, partnerships, and mutual accountability in sectors related to agriculture; increased public and private investments in agriculture; and increased capacity to generate, analyze, and use data, information, knowledge, and innovations. This ATOR presents and discusses progress on 30 of the 40 indicators in the Results Framework.